MONITORING DAN KENDALI KECEPATAN MOTOR UNIVERSAL MENGGUNKAN HUMAN MACHINE INTERFACE (HMI) - Abdul Muis Prasetia; Totok Hariyanto; Abil Huda; Linda Sartika; Fitriani Fitriani (Elektrika Borneo, 2023)
Along with the development of increasingly advanced technology, many tools are created that can facilitate human work. For example, in the industrial world, tools are needed that can increase the efficiency of the production process. Electrical equipment with universal motor propulsion is generally equipped with a speed regulation that is limited to several choices of certain levels. The purpose of the Human Machine Interface (HMI) is to increase the interaction between the machine and the operator through a computer screen display so that the user's need for the system information provided makes physical work easier. The motor speed value (rpm) is read by the microcontroller and then instructs the mosfet driver to change the pwm (duty cycle) value that is read and responds to the universal motor. The encoder sensor reads the universal motor speed and then displays the speed value (rpm) with a graph on the Labview monitor. HMI in industry has a very important role in the monitoring and control system of a production system so that with this system it can save time and labor for observing and controlling each production work station. For the final stage in testing the monitoring and speed control tools the system works well, and has also obtained the gain determination of Kp = 0.25, Ki = 0.2 and Kd = 0 to get the desired set point and response. Then the last experiment was carried out by operating a universal motor from a speed of 1500 rpm, a speed of 2000 rpm and a speed of 2500 rpm. After that the rpm is returned to the point of 2000 rpm.